TEACHER TRAINING FOR INCLUSIVE FRENCH LANGUAGE EDUCATION IN UZBEKISTAN IN THE CONTEXT OF ARTIFICIAL INTELLIGENCE - Kavilova, Tamara (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
The integration of artificial intelligence into education has created new opportunities and challenges for inclusive foreign language teaching. In Uzbekistan, the growing emphasis on inclusive education and digital transformation requires the development of new competencies among French language teachers. This article examines the role of artificial intelligence in preparing teachers for inclusive French language education and analyzes the pedagogical, technological, and methodological implications of AI-supported teaching. Particular attention is given to the development of teacher competencies necessary for supporting students with diverse learning needs, including those with disabilities and different learning profiles. The study proposes a pedagogical framework for integrating artificial intelligence into teacher training and demonstrates how AI tools can enhance accessibility, individualized instruction, and inclusive classroom practices. The findings suggest that artificial intelligence represents a valuable pedagogical resource that supports teachers in creating accessible and inclusive French language learning environments while preserving the essential role of human pedagogical guidance.